Smell and taste changes associated with infection by the SARS-CoV-2 virus from the perspective of affected people, in the municipality of Recife, state of Pernambuco, Northeast, Brazil: A qualitative and quantitative study (Research, Society and Development, 2026)
In December 2019, in the city of Wuhan, China, the World Health Organization (WHO) notified a new disease to COVID-19, which spread rapidly, leading to the death of several lives due to unknown pneumonia, including in Brazil. The aim of this study was to verify the self-perception of people affected by post-covid-19 olfactory and gustatory changes, about the impact of these changes on their lives. An investigation was carried out with a qualitative component, developed using the individual interview technique, employing a case series analysis supported by a questionnaire as a guide, and a quantitative component using descriptive statistics with absolute and relative frequency values. The data were collected from May to December 2022. The sample was obtained by convenience, observing the inclusion and exclusion criteria of the main research, that is, composed of participants aged 18 years or over, diagnosed with COVID-19 and who complained of partial and/or total olfactory and/or gustatory dysfunction and who agreed to participate in this study by signing the Free and Informed Consent Form (TCLE). 8 volunteers participated, and among them 6 complained of olfactory and gustatory dysfunctions, the other 2 only olfactory dysfunction. All revealed the terrible impact of these dysfunctions on their routines, including the impairment of autonomy and self-esteem. The consequences resulting from COVID-19 are present, and it is essential for health professionals to know each one of them so that they can seek control and perhaps restore the health conditions of the population.